За некои недоречености во средновековната историографија и потребата за нивно корегирање - Атанасовски, Александар (Филозофски факултет, Скопје, 2017)
This paper deals with several passages from medieval sources and their improper or incorrect interpretation. Due to the sheer volume of material, we indicate only a portion of these sources and comments on events from the fourth century CE onward, until the end of the eleventh (or, possibly, the late fourteenth) century. This encompasses the events from the times of the Barbarian Migrations, the times of Ss. Cyril and Methodius, as well as the State of Samuel and the events after its fall. In the end, we try to present ideas which would help overcoming outdated notions on certain aspects of medieval history; in particular, the approximation of notions from antiquity to facts from medieval history, especially the habitual attribution of ancient events to national histories in the Middle Ages, an ocurrence is far removed from good historical practice and even historical reality in general.